HAK-HAK POLITIK WANITA DALAM ISLAM - NURHIKMAH NURHIKMAH (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2014)
Islam is a religion that elevates the degree of women in various positions. The position and the honor of women which is equal with men is justified by Islam. One of them is the right of women in politics, such as women's rights in the election, nomination for political office, as well as the right to participate in public affairs. This assumption is the thesis of an understanding of the general arguments contained in the Qur'an and Sunnah, for both men and women. Unless the distinction of their fitrah in the household, one male and one female. Women have their own fitrah such as menstruation, nifas, istihadhah, pregnancy, giving a birth, feeding, parenting and so forth. While men have level of 'qawamah', leadership, responsibility towards their family, and also the right to provide food for the family.